The Number of Days Atmospheric Heights Remain above Basra Governorate during the Period 1955-2021 - Yaseen Yunis Al-Shawi, Researcher. Saja; Abdul Wahab Hassan Al-Asadi , Prof. Dr. Kadhim (Basra studies journal, 2024)
The research examines the impact of the changing number of days of Atmospheric Heights above Basra Governorate through the analysis of surface weather maps at the (1000) millibar level and through observation (GMT12z) during the period (1955-2021) above Basra Governorate. The data were divided into two periods: (1955-1988) and (1988-2021), each divided into three smaller cycles, each lasting (11 years). The extension and secondary centers of these systems were analyzed, their averages and rates of change were determined, tables and graphs were created, and illustrative maps were prepared. The study concluded that Atmospheric Heights typically have low temperatures and low wind speeds, resulting in fewer dust events, while warm high-pressure systems create conditions conducive to dust phenomena.